2018
DOI: 10.1111/jerd.12428
|View full text |Cite
|
Sign up to set email alerts
|

A novel soft tissue thickness measuring method using cone beam computed tomography

Abstract: Objective The aim of this study was to introduce a novel soft tissue thickness measurement method using cone beam computed tomography (CBCT) and to compare the new method with ultrasonic device applications and transgingival probing measurements. Methods Twenty‐five participants (12 female, 13 male, age range, 25‐51 years) were included the study. Soft tissue thickness in lateral incisor, canine, premolar, and molar regions were measured using transgingival probing (group T), ultrasonic device (group U), and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 23 publications
4
41
1
Order By: Relevance
“…The premolar GT3 in the study sample group ranged from 0.9 mm to 1.35 mm. This value is a little higher than the 0.9 mm-to-1.06 mm range reported by Ganji et al [19] using the A-mode US method at a location 3 mm apical to the CEJ in the maxillary premolars and lower than the 1.91±0.41mm reported by Gurlek et al [20] using CBCT at the same locations analyzed in our study. Discrepancies might be caused by differences in the methods, sample sizes and ages as Wara et al [21] reported that participants in a younger age group had significantly thinner mucosa than those in the older age group.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The premolar GT3 in the study sample group ranged from 0.9 mm to 1.35 mm. This value is a little higher than the 0.9 mm-to-1.06 mm range reported by Ganji et al [19] using the A-mode US method at a location 3 mm apical to the CEJ in the maxillary premolars and lower than the 1.91±0.41mm reported by Gurlek et al [20] using CBCT at the same locations analyzed in our study. Discrepancies might be caused by differences in the methods, sample sizes and ages as Wara et al [21] reported that participants in a younger age group had significantly thinner mucosa than those in the older age group.…”
Section: Discussioncontrasting
confidence: 65%
“…Clinical B-mode US examination Fifty periodontally healthy participants (25 men; mean age 25.8±4.4 [range, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]] years) and their 400 premolar teeth were included in this study. The premolars were imaged with the 15 MHz B-mode US device from the buccal side.…”
Section: Measurements Using 15 Mhz B-mode Us In Human Participants Stmentioning
confidence: 99%
“…Hence, the examination paradigm and diagnostic standard must be established for gingival phenotype assessment based on multiple clinical scenarios. To date, several studies have compared ultrasonic devices or CBCT as measuring tools with transgingival probing individually 21–24 . However, no systematic review has evaluated gingival thickness measurement methods.…”
Section: Introductionmentioning
confidence: 99%
“…The GT thickness can be measured with the use of invasive methods such as a needle, an endodontic tool, or a periodontal probe, or with the use of radiological methods like parallel profile radiographs and cone-beam computed tomography (CBCT) [ 12 – 16 ]. Noninvasive methods include using an ultrasonic device and optical coherence tomography [ 13 , 16 20 ]. Measurements of the WKT are most often carried out using a periodontal probe calibrated every 1 mm [ 20 ].…”
Section: Introductionmentioning
confidence: 99%